Lead optimization based design, synthesis, and pharmacological evaluation of quinazoline derivatives as multi-targeting agents for Alzheimer's disease treatment - Verma A.; Waiker D.K.; Singh N.; Singh A.; Saraf P.; Bhardwaj B.; Kumar P.; Krishnamurthy S.; Srikrishna S.; Shrivastava S.K. (My University, 2025)
The complexity and multifaceted nature of Alzheimer's disease (AD) have driven us to further explore quinazoline scaffolds as multi-targeting agents for AD treatment. The lead optimization strategy was utilized in designing of new series of derivatives (AK-1 to AK-14) followed by synthesis, characterization, and pharmacological evaluation against human cholinesterase's (hChE) and β-secretase (hBACE-1) enzymes. Amongst them, compounds AK-1, AK-2, and AK-3 showed good and significant inhibitory activity against both hAChE and hBACE-1 enzymes with favorable permeation across the blood-brain barrier. The most active compound AK-2 revealed significant propidium iodide (PI) displacement from the AChE-PAS region and was non-neurotoxic against SH-SY5Y cell lines. The lead molecule (AK-2) also showed Aβ aggregation inhibition in a self- and AChE-induced Aβ aggregation, Thioflavin-T assay. Further, compound AK-2 significantly ameliorated Aβ-induced cognitive deficits in the Aβ-induced Morris water maze rat model and demonstrated a significant rescue in eye phenotype in the Aꞵ-phenotypic drosophila model of AD. Ex-vivo immunohistochemistry (IHC) analysis on hippocampal rat brains showed reduced Aβ and BACE-1 protein levels. Compound AK-2 suggested good oral absorption via pharmacokinetic studies and displayed a good and stable ligand-protein interaction in in-silico molecular modeling analysis. Thus, the compound AK-2 can be regarded as a lead molecule and should be investigated further for the treatment of AD. © 2024 Elsevier Masson SAS